The Cumulative Effects of Plant Extract Tavri Shrub (Daphne Mucronata) on Some Biological Aspects of Mosquito Culex Molestus Forskal - Abdulmajeed, Anas M.; Al-Chalabi, Badia'a M. (Science Journal of University of Zakho, 2017)
The present study was performed to evaluate the toxicity and biological activity of ethanolic extract of the plant tavri shrub (Daphne mucronata) which is widely abundant in Iraqi Kurdistan region against the mosquito (Culex molestus Forskal) using different concentrations (0.25- 7.5 mg/ml). The plant extract  significantly affected the survival rate of all immature stages, prolonged their developmental period, preoviposition period, reduced egg productivity and hatchability, caused growth abnormalities, led to the appearance of intermediates and the adult failed to emerge. The cumulative effect of the Plant extract significantly affected the hatchability of eggs, mortality rate and elongation the duration of the larvae and pupae of C. molestus. The adult emergence and most of the vital biological activities of the emerging females including preoviposition period, fecundity and fertility were obviously affected.  Also the extract caused various morphological deformations at different developmental stages.
Keywords: Ethanolic; Daphne Mucronata; Mosquito; Culex molestus Forskal; Morphology